Transcranial Direct Current Stimulation Enhances Exercise Performance: A Mini Review of the Underlying Mechanisms - Jaberzadeh, Shapour; Zoghi, Maryam (Frontiers in Neuroergonomics, 2022)
Exercise performance (EP) is affected by a combination of factors including physical, physiological, and psychological factors. This includes factors such as peripheral, central, and mental fatigue, external peripheral factors such as pain and temperature, and psychological factors such as motivation and self-confidence. During the last century, numerous studies from different fields of research were carried out to improve EP by modifying these factors. During the last two decades, the focus of research has been mainly moved toward the brain as a dynamic ever-changing organ and the ways changes in this organ may lead to improvements in physical performance. Development of centrally-acting performance modifiers such as level of motivation or sleep deprivation and the emergence of novel non-invasive brain stimulation (NIBS) techniques such as transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS) are the key motives behind this move. This article includes three sections. Section one provides an overview of the mechanisms behind the reduction of EP. The main focus of the second section is to provide a brief description of the effects of anodal tDCS on maximal and submaximal types of exercise and finally, the last section provides description of the mechanisms behind the effects of tDCS on EP.